2021
DOI: 10.1186/s12883-021-02288-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased cerebrospinal fluid adenosine 5'-triphosphate in patients with amyotrophic lateral sclerosis

Abstract: Background Extracellular adenosine 5'-triphosphate (ATP) has been suggested to cause neuroinflammation and motor neuron degeneration by activating microglia and astrocytes in amyotrophic lateral sclerosis (ALS). Since we have developed a highly sensitive ATP assay system, we examined cerebrospinal fluid (CSF) ATP levels in patients with ALS whether it can be a useful biomarker in ALS. Methods Forty-eight CSF samples from 44 patients with ALS were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In advanced ALS patients, there is a significant increase in extracellular ATP in CSF samples compared to non-ALS controls . In conjunction, the P2X 7 R is upregulated on activated microglial cells from post-mortem ALS spinal cord specimens, presumably representing the end stage of disease .…”
Section: Role Of the P2x7 Receptor In Amyotrophic Lateral Sclerosismentioning
confidence: 97%
“…In advanced ALS patients, there is a significant increase in extracellular ATP in CSF samples compared to non-ALS controls . In conjunction, the P2X 7 R is upregulated on activated microglial cells from post-mortem ALS spinal cord specimens, presumably representing the end stage of disease .…”
Section: Role Of the P2x7 Receptor In Amyotrophic Lateral Sclerosismentioning
confidence: 97%
“…On the other hand, increased ATP levels in ALS patients CSF were measured [ 129 ]. Importantly, Apolloni et al demonstrated that the antagonism of P2X7 receptor in a SOD1-G93A mouse model of ALS ameliorates the early symptomatic phase of the disease by reducing microglia-related pro-inflammatory markers and autophagy [ 130 ].…”
Section: Damage-associated Molecular Patterns Released From Mitochond...mentioning
confidence: 99%
“…On the other hand, increased ATP levels in ALS patients CSF were measured [125]. Importantly, Apolloni et al demonstrated that the antagonism of P2X7 receptor in a SOD1-G93A mouse model of ALS ameliorates the early symptomatic phase of the disease by reducing microglia-related pro-inflammatory markers and autophagy [126].…”
Section: Atpmentioning
confidence: 99%